(untitled) (Research, Society and Development, 2021)
Scientific communication coupled with knowledge is of paramount importance for the development of contemporary society and consequently a liberating act from the moment it is managed as a determining strategic value and a good that must be shared. This study aimed to investigate how students in the first year of high school integrated with Vocational and Technological Education (EFA) through scientific communication tools tend to behave in terms of mastery and appropriation of these tools where a workshop was held with the intention to develop basic skills on various ways of accessing scientific communication through databases, formalize this knowledge by completing / updating the Lattes curriculum and knowing how the research project is structured through ABNT NBR 15287: 2011. Data collection was carried out by analyzing Bardin’s content and applying a questionnaire so that we could observe the evolution and progress of activities during the workshop. Among the workshop’s proposals, it was found that the themes addressed to this specific audience were considered to be unprecedented since the vast majority had little or no knowledge of the subjects, with the workshop being the first contact with the themes of scientific communication. Through data collection we were able to understand that when scientific communication is encouraged even in adolescence, these young people have the power to understand, interpret and create a critical sense through reliable sources generating from this tripod (understand, interpret and criticize) others possible themes building and contributing to a more appropriate and qualified knowledge for society.